Structural and functional characterization of peptides derived from the carboxy-terminal region of a defensin from the tick Ornithodoros savignyi - Gaspar, A.R.M. (Anabella Regina Marques) (University of Pretoria, 2014)
Dissertation (MSc)--University of Pretoria, 2013.